THE ROLE OF GOVERNMENT IN IMPLEMENTATION OF CONSERVATION PARTNERSHIPS IN SUMBER SARI FOREST FARMER GROUP PESAWARAN REGENCY - Agatha Shelly Albarez S; Hari Kaskoyo; Slamet Budi Yuwono; Arief Darmawan (Jurnal Belantara, 2025)
The government has an important role in implementing conservation partnerships as an effort to balance sustainable forest utilization. The purpose of this study is to analyze the role of government in implementing the conservation partnership program in KTH Sumber Sari, Pesawaran Regency. The collected data were analyzed descriptively and the measurement of the government's role used a Likert scale. The results showed that the government's role in implementing the conservation partnership was considered to be quite instrumental with an average overall score of 3.22 or 80%. However, there are several aspects that need improvement, especially in involving farmers in the planning process, monitoring and evaluation activities, and responding to constraints faced by farmers. The government is expected to improve collaboration with forest farmers to ensure the implementation of conservation partnerships can run more effectively and sustainably.